2009
DOI: 10.1016/j.bbapap.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of protein tyrosine nitration after ischemia reperfusion injury: Mitochondria as the major target

Abstract: Endothelial nitric oxide synthase-derived NO and its derivative, peroxynitrite (ONOO-), suppresses oxygen consumption by nitration of mitochondrial proteins after reperfusion. However, very few nitrated proteins are identified to date. In this paper, ischemia/reperfusion (I/R) injury was induced in mouse heart by ligation and release of the left anterior descending coronary artery. Western blotting showed that tyrosine nitration was higher in I/R hearts. Nitrated proteins were identified by capillary-liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 54 publications
2
87
0
2
Order By: Relevance
“…29,34 The presence of nitrated proteins has been implicated in many disease states including I/R injury. 35,36 Our data showed that the tissue protein levels of nitrotyrosine were much higher after I/R relative to the sham-operated rats. Therefore, we hypothesized that the nitrated proteins may experience a loss of function, which attenuates protective roles and contributes to I/R-associated vascular injury.…”
Section: Discussionmentioning
confidence: 61%
“…29,34 The presence of nitrated proteins has been implicated in many disease states including I/R injury. 35,36 Our data showed that the tissue protein levels of nitrotyrosine were much higher after I/R relative to the sham-operated rats. Therefore, we hypothesized that the nitrated proteins may experience a loss of function, which attenuates protective roles and contributes to I/R-associated vascular injury.…”
Section: Discussionmentioning
confidence: 61%
“…Impaired cellular oxidative metabolism is observed in patients with mutations on the NDUFS1 gene. 43 The Rieske subunit is also a component of the iron-sulfur fragment of cytochrome bc1 complex and transfers electrons to cytochrome c. Liu et al 44 showed that 4 subunits from the ETC including the Rieske subunit were remarkably nitrated at the tyrosine residues in the ischemicreperfused heart. Thus, deacetylation of these proteins might protect them from detrimental protein modifications during ischemia/reperfusion.…”
Section: Shinmura Et Al Cr Primes Mitochondria For Ischemic Stress 403mentioning
confidence: 99%
“…ROS production increases during ischemia until the O 2 is exhausted; then, it may further increase in early reperfusion (17,89,191,220,396,401). In ischemic hearts, the pH falls to 6.8 or less, but abruptly rises with reperfusion.…”
Section: Executive Summary and Conclusionmentioning
confidence: 99%
“…This inhibition can be transformed into irreversible alterations of respiratory chain when NO reacting with O 2 -generates a great amount of ONOO -, an RNS that can produce irreversible nitration of proteins, including proteins from the oxidative phosphorylation system (18,220,362,391). Under certain conditions, such as scarcity of substrate and/or cofactors, NOS can become uncoupled, resulting in the generation of O 2 -and/or OH , instead of NO (18,379).…”
Section: Ros and Rns Such As Omentioning
confidence: 99%